Mold growth on spruce and pine samples in steady state conditions: Time of germination and maximum coverage - Pavla Ryparová; Kamil Staněk; Jan Richter; Pavel Kopecký (Acta Polytechnica CTU Proceedings, 2022)
Wood is a material that is environmentally friendly and has minimal carbon impact. The durability of wood depends on ambient environmental conditions. This article deals with mold growth on wood samples under constant relative humidity (75 %; 87 %; 95 % RH) and temperature (23 °C). Pine and spruce samples with surfaces oriented along the three principal anatomical directions of wood were prepared. The occurrence of mold was studied by regular microscopic observations. The mold consortium was a mixture of Penicillium sp., Aspergillus sp., and Alternaria sp. The first signs of mold growth on pinewere observed after 7 days for 87 % RH and 12 days for 95 % RH, regardless the surface orientation. Molds on spruce began to grow in 12 to 26 days at 95 % RH in dependence on surface orientation: at first on tangential surface, then on transversal surface, and finally on radial surface. The lower relative humidity of 87 % resulted in a shorter germination time: 7 days for tangential and radial surfaces, and 21 days for transversal surface.